Medium Density Fiberboard Machining and Wear Behavior of Injection‐Molded Ceramic Composite Wood Cutting Tools. Issue 1 (26th July 2013) - Sommer, Frank; Talpeanu, Dan; Kern, Frank; Gadow, Rainer; Heisel, Uwe
<x xml:space="preserve">Abstract</x> Wear behavior of four different ceramic composite cutting tools was studied in peripheral milling of medium density fiberboard. Tools were previously manufactured by near net‐shape ceramic injection molding with subsequent debindering and sintering. Cutting edge rounding and recession were investigated for defined cutting parameters and distinct cutting distances. Cutting forces were measured dependent on tool material and feed travel. Wear characteristics of ceramic cutting tools were investigated by SEM. Ceramic injection‐molded tools were successfully applied in wood‐machining operations. Wear mechanisms changed with different ceramic composites used. Results of microchamfered ACY tools showed superior lifetime compared with standard WC–Co tools.